2020
DOI: 10.3390/cancers12010175
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Nanoparticles for the Treatment of Malignant Gliomas

Abstract: Malignant gliomas are one of the deadliest forms of brain cancer and despite advancements in treatment, patient prognosis remains poor, with an average survival of 15 months. Treatment using conventional chemotherapy does not deliver the required drug dose to the tumour site, owing to insufficient blood brain barrier (BBB) penetration, especially by hydrophilic drugs. Additionally, low molecular weight drugs cannot achieve specific accumulation in cancerous tissues and are characterized by a short circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 216 publications
0
53
0
Order By: Relevance
“…With this strategy in mind, we have developed and characterized a CXCL12 delivery system based on Alg/Chit NPs. NPs made of polyelectrolyte complexes such as Alg/Chit are particularly adapted for addressing molecules to the brain tissue and have potential to treat gliomas [42,43]. They can easily be freeze-dried and reconstituted without affecting the size, release capacity, and bioactivity of the solute contained within [31].…”
Section: Discussionmentioning
confidence: 99%
“…With this strategy in mind, we have developed and characterized a CXCL12 delivery system based on Alg/Chit NPs. NPs made of polyelectrolyte complexes such as Alg/Chit are particularly adapted for addressing molecules to the brain tissue and have potential to treat gliomas [42,43]. They can easily be freeze-dried and reconstituted without affecting the size, release capacity, and bioactivity of the solute contained within [31].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, revealing the feasible molecular mechanisms contributing to the formation and progression of this tumor might be a pivotal step in the generation of new and more effective precision therapies [18][19][20][21]. In this study, we explored RPS27L overexpression in gliomas and demonstrated that RPS27L expression increased as an increase in tumor grade and that RPS27L was associated with the overall survival of patients, which suggested that RPS27L played an important role in glioma malignancy.…”
Section: Discussionmentioning
confidence: 92%
“…These polymeric nanoparticles are used as carriers for different drugs such as in chemotherapy, which are either adsorbed on the surface or encapsulated within the nanoparticles. These improve the release kinetics, the compatibility with some active agents, have no oxidation issues (as with phospholipids), and enhance shelf-life [ 82 ]. Other studies [ 63 , 68 ] also detected VEGF in antiangiogenic therapy but did not quantify the protein expression after therapy.…”
Section: Discussionmentioning
confidence: 99%